PERSONALITY FACTORS AS BASIC ELEMENTS OF THE ESTONIAN YOUTH WORKERS´PROFESSIONAL GROWTH - Veigel, Maarika (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article dealt with one aspect of the professional growth basic elements. The issue of the Estonian Youth Centers youth workers´ professionality has been relevant for many years, as employees often exchange. Expectations for youth work as a promotion of non-formal education are high. There is no research that explained the issues related to the youth workers professional growth, including personal factors. The theoretical framework of the research created Ruohotie, Tamm, Clarke and Hollingsworth concepts of professional growth. The purpose of this research was brought to the light youth work specialists´ opinions about the personal factors of the professional growth. For qualitative data collection semi-structed interviews were conducted with 35 Estonian youth work specialists in 2016-2018. The results showed that in eight key-topics important opinions were received. Most attention should be given further to the youth workers´ internal motivation, treatment and professional identity. Mostly were explained the high expectations to the youth work generally. Interviews revealed a different commitment to everyday work, that could have resulted from their different education and professional training or attitudes towards education. The needs for further clarification are: occupational and organizational elements of youth workers professional growth.